MINE WASTE DUMP FAILURE BEHAVIOUR MODEL BASED ON STATICAL DATA - Putra, Galih Zoya Manggala; Sadewa, Lintang Putra; Putuhena, Yuli Amalia (PERHAPI, 2023)
To enhance the safety operation over open pit mines around the world, slope monitoring program has now become a mandatory campaign. By utilizing various instruments and monitoring strategy, this campaign is expected to help the slope failure risk mitigation is enhanced by delivering the most precise information as consideration before taking the best decision.Slope stability radar is nowadays considered as the most sophisticated and accurate slope monitoring technology, as it enables to deliver slope deformation in submillimetre accuracy. The deformation data collected by slope stability radar is a precious information that can be used to analyse and interpret to understand the slope behaviour in certain location with certain geological setting. This data can be the consideration in determining the alarm threshold setting.Statistical method using Anderson Darling Fitting test is applied to each parameter obtained from several failure back analysis in mine waste dump failure. The sample mean values then used to create an empirical model of a mine waste dump failure behaviour, which consists of several sequences. There are three consecutive sequences of a waste dump slope failure, which are transitional, progressive, and failure to post failure. The fitting test address that each sequence own variable with different distribution pattern and sample mean values. In the end, the empirical model compared to actual data lead to conclusion that the sample mean values of each parameter is very well represented.